Implementasi Game Edukasi Dalam Menunjang Pembelajaran Pengenalan Hewan Mamalia dan Reptil Menggunakan Rpg Maker (Studi Kasus SDN Tunggakjati IV - Putera, Audy Sukma; Sari, Betha Nurina; Susilawati, Susilawati (Jurnal Ilmiah Wahana Pendidikan, 2025)
Learning is an action taken by educators to provide knowledge and create an effective and efficient learning environment. Natural Science (IPA) is an important scientific discipline that studies living things and their life processes, and is always developing, IPA involves observing the universe with proper procedures to reach conclusions, and includes flora and fauna, which are important at every level of education. This research aims to implement RPG games as learning media to distinguish mammals and reptiles in an interesting way and develop educational games for this purpose. This research utilizes the Multimedia Development Life Cycle (MDLC) methodology, which consists of six stages: concept, design, material collection, assembly, testing, and distribution. MDLC is effective for developing simple multimedia applications. The use of MDLC in educational games increases children's learning interest and understanding, with results showing an increase in student success from 43.75% to 86%, which categorizes the performance as GOOD (B). This study successfully facilitated students in understanding the differences between mammals and reptiles through educational games. The test results showed a significant difference between the scores before and after using the application.